The neotype of the type species of the neotropical iguanian genus Phymaturus : a critical commentary on a recent opinion of the International Commission on Zoological Nomenclature - Cei, José Miguel (2006)
The fundamental weakness of the Opinion 2118 (Case 3225) of the International Commission on Zoological Nomenclature is discussed. A former documented research established the Teiid identity of Lacerta palluma Molina 1782, a misidentified type species of the Iguanian genus Phymaturus, now confirmed by the Opinion. The holotype of the iguanian synonym Centrura flagellifer (Bell, 1843) is proposed as neotype of Phymaturus palluma (Molina, 1782), the misidentified type species of Gravenhorst 1837. Such a neotype should be named Phymaturus flagellifer (Bell, 1843) in agreement to the real taxonomic position of the Molina’s species, a Teiid Callopistes, a lacertilian genus strikingly distant from the iguanid genus Phymaturus.